Organizational identification and “currencies of exchange”: integrating social identity and social exchange perspectives - Tavares, S. M.; van Knippenberg, D.; van Dick, R. (Journal of Applied Social Psychology, 2016)
We integrate social exchange and social identity perspectives to propose and test the prediction that depending on their level of organizational identification, people may reciprocate the received organizational support using different “currencies of exchange” – reducing turnover intentions or, instead, engaging in extra-role behavior. Specifically, the relationship of perceived organizational support (POS) with turnover intentions is proposed to be stronger with lower identification, whereas POS is proposed to be more closely related to extra-role behavior with higher organizational identification. These predictions were supported in a cross-sectional survey of N = 1000 employees of a financial services firm. These results speak to the added value of integrating the social exchange perspective with its roots in applied psychology and the social identity perspective with its roots in social psychology in understanding the employee-organization relationship.